ANTECEDENTES Y FORMACIÓN PROFESIONAL DEL OPTÓMETRA EN COLOMBIA (2018)
The arrival of the first optometrist to the country from American and European Schools with optical and refraction studies, dates from 1914. In 1933, the first decrees (449 and 1291), that regulate the profession in Colombia, are issued for the whole National territory.In 1952, is created the Colombian Graduated Optometrists Federation (Fedopto), which reunited the professionals with graduated studies in order to promote the academic activities and the defense of the profession. After that, in 1954, the decree-law 0825 from March 23th, modifies the other one, 1921, defending the profession's field of action.With this one, the Optometry became an autonomous and independent profession with social projection, defined as «... profession devoted to determination and measurement of the refraction, accommodation and mobility defects of the human vision. The trial, prescription and adaptation of the lens that correct these defects. The conditioning of the contact lens, ocular prothesis devices and the practice of orthoptic exercises, without using drugs, medicine or surgery».